The Glucocorticoid-Induced Leucine Zipper (GILZ) Is Essential for Spermatogonial Survival and Spermatogenesis - Romero, Y. (Sex Dev, 2012)
Spermatogenesis relies on the precise regulation of the self-renewal and differentiation of spermatogonia to provide a continuous supply of differentiating germ cells. The understanding of the cellular pathways regulating this equilibrium remains unfortunately incomplete. This investigation aimed to elucidate the testicular and ovarian functions of the glucocorticoid-induced leucine zipper protein (GILZ) encoded by the X-linked Tsc22d3 (Gilz) gene. We found that GILZ is specifically expressed in the cytoplasm of proliferating spermatogonia and preleptotene spermatocytes. While Gilz mutant female mice were fully fertile, constitutive or male germ cell-specific ablation of Gilz led to sterility due to a complete absence of post-meiotic germ cells and mature spermatozoa. Alterations were observed as early as postnatal day 5 during the first spermatogenic wave and included extensive apoptosis at the spermatogonial level and meiotic arrest in the mid-late zygotene stage. Overall, these data emphasize the essential role played by GILZ in mediating spermatogonial survival and spermatogenesis.